Iraqi EFL University Students' Performance of Articles: A Phono-syntactic Study - Mahdi Yousif, Salah; Ameer Yousif, Sinan; Chassab Jabir, Azhar (International Journal of Psychosocial Rehabilitation, 2020)
Writing or uttering a statement like the following "College demands change" seems, to most speakers and learners, to be grammatically unacceptable and vague. The absence of words like (a, the, this) is the main reason of this ambiguity. The addition of an indefinite article (a) can make this statement valid, or at least, acceptable for them. Speakers always seek for making their utterances clear and understood by listeners and readers. This is usually done by adding certain words that make their utterances or phrases clear. The word (house), for instance, has an indefinite reference in the following Noun Phrase (NP):1-A house in some other NPs, it may have a more definite one as in:2-The white house, my house, that house, the big house,etc.The words in italics are the main cause behind this clarity and definiteness. Such words are called "Determiners" due to the function they perform, i.e. determining the head word (noun) which they precede. Determiners play a central role in languages in that they make NPs have a definite or indefinite reference. Due to the important role Determiners play, the present research has come into existence to tackle them focusing on how Advanced Iraqi Learners (AILs) of English can recognize and use them in forming various NPs. Due to the various types and great number of Determiners, special emphasis will be given here to definite and indefinite articles since they represent the focus of this research. Some of their essential uses will be tested to find out the difficulties AILs face concerning their recognition and production. As teachers, the researchers have themselves traced this difficulty. A two-part test has been built for this purpose, and the responses have statistically been treated to come to scientifically accurate results.